Tracing the social project of Networked Learning - Bligh, Brett; Lee, Kyungmee (Proceedings of the International Conference on Networked Learning, 2024)
This paper provides an outline of Networked Learning as a social project. Using a theoretical framework derived from activity theory, the paper reconstructs the existing narratives in key texts on a principled basis and traces the project through three phases whose core concepts, in turn, are educational openness, connections between network elements, and connections for particular purposes. Against the backdrop of an ongoing discussion of the meaning and nature of Networked Learning, the aim is to show how concepts of networked learning respond to social predicaments and are used as the basis for institution building, and to illustrate the kind of dynamics that have led to change in the past — as a potential guide to addressing upcoming challenges.